2016
DOI: 10.4236/ojn.2016.61001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factor of Diabetic Foot Ulcers in a Regional Hospital, Eastern Indonesia

Abstract: Indonesia is one of the top ten diabetes mellittus (DM) countries. However as the main complication of DM, there was lack of studies related to diabetic foot ulcer (DFU). Thus, the aim of this study was to survey the prevalence of DFU risk factors and DFU among type 2 diabetes mellitus (T2DM) patients. An epidemiological study was conducted at an outpatient endocrine clinic in a regional hospital, eastern Indonesia. All T2DM participants attending research setting that were ≥ 18 years were included. Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
1
28

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 28 publications
5
53
1
28
Order By: Relevance
“…In the UK, Greece, and India, the prevalence of DFUs is 1.7%, 4.8%, and 3.6%, respectively . In contrast, the prevalence of DFUs in eastern Indonesia is 12% …”
Section: Development Of the New Dfuasmentioning
confidence: 97%
“…In the UK, Greece, and India, the prevalence of DFUs is 1.7%, 4.8%, and 3.6%, respectively . In contrast, the prevalence of DFUs in eastern Indonesia is 12% …”
Section: Development Of the New Dfuasmentioning
confidence: 97%
“…A previous study reported that 85% of lower limb amputations in the US are due to diabetic foot ulcer (Driver, Fabbi, Lavery, & Gibbons, 2010). A study by Yusuf et al (2016) reported a prevalence of diabetic foot ulcer in Sulawesi of 12%. This number is higher compared to other countries, even China, which has only a prevalence of about 5.9% (Yusuf et al, 2016).…”
mentioning
confidence: 99%
“…A study by Yusuf et al (2016) reported a prevalence of diabetic foot ulcer in Sulawesi of 12%. This number is higher compared to other countries, even China, which has only a prevalence of about 5.9% (Yusuf et al, 2016). Sulawesi's prevalence might be higher since many cases of diabetic foot ulcer in Indonesia have been unreported.…”
mentioning
confidence: 99%
“…It is predicted that Indonesia will become number six by 2030 (Shaw, Sicree and Zimmet, 2010). Soewondo, Ferrario and Tahapary (2013) revealed that the prevalence of patients with DM in Indonesia had increased by 11 % over 19 years, although this figure is likely to be higher since there are many unreported cases (Yusuf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%